PEMANFAATAN SIMBIOSIS MIKROALGA Chlorella sp DAN EM4 UNTUK MENURUNKAN KADAR POLUTAN LIMBAH CAIR SAGU - Simatupang, Dewi; Restuhadi, Fajar; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aimed of the research was to got the best combination of EM4 and Chlorella sp in reduced pollutant sago liquid waste. This research was used a Completely Randomized Design (CRD) non factorial with five treatments and three replications to obtain 15 experimentals unit. Formulation treatments were A0 (without addition EM4), A1(addition 5 ml EM4), A2 (additon 10 ml EM4), A3 (addition 15 ml EM4), A4 (addition 20 ml EM4). Data obtained was Analyzed Statistically Using Analysis of Variance (ANOVA). If F calculated equal to or greater than F table then proceed to test Duncan’s MultipleNew Range Test (DNMRT) at level 5%. The result showed that the addition of 20 ml EM4 effectively reduce levels of sago waste pollutant as much as 90,2% COD, 83% BOD, and 81% TSS. The other side pH was increase from 4,17 to 7,07. Keywords: EM4, Chlorella sp, sago liquid waste, COD, BOD, TSS, pH.